Equatorial Ionospheric Anomaly (EIA) and comparison with IRI model during descending phase of solar activity (2005– 2009) - Singh, A.K. (2014)
The ionospheric variability at equatorial and low latitude region is known to be extreme as compared to mid latitude region. In this study the ionospheric total electron content (TEC), is derived by analyzing dual frequency Global Positioning System (GPS) data recorded at two stations separated by 325 km near the Indian equatorial anomaly region, Varanasi (Geog latitude 25°, 16/ N, longitude 82°, 59/ E, Geomagnetic latitude 16°, 08/ N) and Kanpur (Geog latitude 26°, 18/ N, longitude 80°, 12/ E, Geomagnetic latitude 17°, 18/ N). Specifically, we studied monthly, seasonal and annual variations as well as solar and geomagnetic effects on the equatorial ionospheric anomaly (EIA) during the descending phase of solar activity from 2005 to 2009. It is found that the maximum TEC (EIA) near equatorial anomaly crest yield their maximum values during the equinox months and their minimum values during the summer. Using monthly averaged peak magnitude of TEC, a clear semi-annual variation is seen with two maxima occurring in both spring and autumn. Results also showed the presence of winter anomaly or seasonal anomaly in the EIA crest throughout the period 2005–2009 only except during the deep solar minimum year 2007–2008. The correlation analysis indicate that the variation of EIA crest is more affected by solar activity compared to geomagnetic activity with maximum dependence on the solar EUV flux, which is attributed to direct link of EUV flux on the formation of ionosphere and main agent of the ionization. The statistical mean occurrence of EIA crest in TEC during the year from 2005 to 2009 is found to around 12:54 LT hour and at 21.12° N geographic latitude. The crest of EIA shifts towards lower latitudes and the rate of shift of the crest latitude during this period is found to be 0.87° N/per year. The comparison between IRI models with observation during this period has been made and comparison is poor with increasing solar activity with maximum difference during the year 2005.